Poseidon's arrow eaudiobook - Cussler, Clive (Dirk Pitt, 2016)
With adventures plumbing the depths of the oceans, Clive Cussler's Dirk Pitt novels always rise to the top of the New York Times best-seller list. An unparalleled white-knuckle affair, Poseidon's Arrow finds Pitt on his most dangerous mission yet. With a key part of an experimental sub missing, Pitt and his NUMA team race against time to prevent the technology from falling into the wrong hands.